Design of choline chloride modified USY zeolites for palladium-catalyzed acetylene hydrochlorination. Issue 16 (29th March 2022) - Long, Zeqing; Wang, Lu; Yan, Haijun; Si, Jianxin; Zhang, Meng; Wang, Jide; Zhao, Ling; Yang, Chao; Wu, Ronglan
Abstract : USY zeolites (USY) were applied to design and synthesize palladium-based heterogeneous catalysts for exploring an efficient non-mercuric catalyst for acetylene hydrochlorination. Abstract : USY zeolites (USY) were applied to design and synthesize palladium-based heterogeneous catalysts for exploring an efficient non-mercuric catalyst for acetylene hydrochlorination. Choline chloride (ChCl) was selected as the nitrogen-containing ligand to modify the Pd@USY catalysts and the proposed Pd@15ChCl@USY catalyst exhibited obviously the best catalytic performance with a stable acetylene conversion and vinyl chloride selectivity of over 99.0% for more than 20 h. According to the results of characterization and the density functional theory calculations, it is indicated that the addition of ChCl can significantly inhibit the agglomeration and loss of the Pd active species, prevent carbon deposition and enhance the ability of HCl and C2 H2 adsorption and C2 H3 Cl desorption, resulting in promoting the catalytic performance of Pd@USY catalysts during the acetylene hydrochlorination reaction.